Fake news knowledge profile in Brazil during the COVID-19 pandemic (Research, Society and Development, 2021)
During the COVID-19 pandemic, a lot of false information spread through social networks, reaching different community groups, and contributing to the failure in the prevention and correct treatment of the disease. This study aimed to outline the profile of people who received fake news related to health during the SARS-CoV-2 pandemic in 2020. This is a descriptive study with a quantitative approach carried out by health academics through a self-administered questionnaire made on Google Forms. A sample of 501 participants was obtained to analyze the participant sociodemographic profile, the content, and the most used ways of receiving fake news. The results indicate that the most received content by the participants was about health, followed by politics. According to the study, traditional communication media are the most reliable source in the search for information among participants, while WhatsApp and Facebook were cited as the most used social media in the dissemination of fake news, with the least reliable news. There is a need for further studies on this topic, to demonstrate which sociodemographic factors, influence the sharing of fake news.